Husband-Wife Interaction, Social Support, Work-Family Balance, and Marital Satisfaction Among Female Teacher Families with Toddler-Aged Children - Purnama, Nurjanah; Krisnatuti, Diah; Johan, Irni Rahmayani (Journal of Educational, Health and Community Psychology, 2025)
Marital satisfaction can be influenced by the quality of husband-wife interaction and the availability of social support. This quantitative study aims to examine the effects of husband-wife interaction, social support, and work-family balance on the marital satisfaction of female elementary school teachers with children under five years old in Bogor City. A total of 179 respondents participated in this study, consisting of 83 public and 96 private elementary school teachers. Data were collected through structured interviews and questionnaires. The analysis employed an independent sample t-test, correlation analysis using the Statistical Package for the Social Sciences (SPSS), and path analysis using Smart Partial Least Squares (SmartPLS). The findings revealed significant differences in husband-wife interaction and work-family balance between public and private school teachers. Additionally, husband-wife interaction, social support, and work-family balance were significantly correlated with marital satisfaction. Furthermore, husband-wife interaction and social support were found to have a significant effect on marital satisfaction. These findings suggest the need for the Ministry of Education and Culture of the Republic of Indonesia to re-evaluate the workload and responsibilities assigned to both public and private school teachers, particularly those with young children, in order to support a more optimal work-family balance and enhance marital satisfaction.